Land Use/Land Cover Dynamics and its Implication on Sustainable Land Management in Wallecha Watershed, Southern Ethiopia (Global Journal of Science Frontier Research, 2016)
This study was conducted at Wallecha Watershed in the middle course of Bilate River Basin in Wolayitta Zone, Southern Ethiopia with the main objective of assessing the patterns of spatial and temporal dynamics of land use/land cover (LU/LC) and implications on sustainable land management (SLM). The study area was covered 10116.7ha, and had previously undergone substantial LU/LC changes. The changes in LU/LC which occurred between 1984 and 2010 were monitored in a context of geographical information system (GIS) and remote sensing (RS). The Lands at imageries of 1984, 2000 and 2010 were used to produce three land cover maps of the respective years using GIS and RS techniques with field verification. Changes in the density of vegetation cover and land degradation over time in the watershed were also estimated with the help of Normalized Difference Vegetation Index (NDVI). The general trend was observed as there is decrease in forest lands and shrub-grasslands at a rate of 34.27and 15.63ha per year respectively, and a decrease in degraded lands at a rate of 7.63 ha per year.
Keywords: dynamics; land cover; land use; watershed; SLM